Ghana's commercial bank
This booklet contains the speech made by Mr. F.K.D. Goka, Minister of Finance, at the opening of the 'Bank Week', the papers presented during the symposium which formed part of the tenth anniversary celebration and a short history of the Bank.
osc 18/01/2019
Loans
Keywords: Banks; Ghana